The Professional Quality of Life Among Nurses in Saudi Arabia: A Multi-Centre Study - Algamdi MM (Dove Medical Press, 2022)
Maaidah M Algamdi Department of Nursing, Faculty of Applied Medical Sciences, University of Tabuk, Tabuk, Saudi ArabiaCorrespondence: Maaidah M AlgamdiDepartment of Nursing, Faculty of Applied Medical Sciences, University of Tabuk, Tabuk, Saudi Arabia, Tel +966560091866, Email ialghamdi@ut.edu.saBackground: The nursing profession in Saudi Arabia requires attention and support. Assessing Saudi nurses' professional quality of life (ProQOL) is crucial for their future nursing careers and the future of Saudi health care.Aim: To investigate the level of ProQOL among nurses in Saudi Arabia and its association with personal and professional sociodemographic variables.Methods: A cross-sectional descriptive study was conducted on a sample of 334 Saudi nurses working in three hospitals and multiple primary health centers. Descriptive analysis, Mann-Whitney U and Kruskal-Wallis tests were used to determine the significant association between sample sociodemographic variables and levels of ProQOL.Results: A significant difference between compassion satisfaction (CS) and nurses' age (p-value = 0.008) and years of experience (p-value = 0.012) was confirmed. The job location (p-value < 0.001), nurses' department (p-value = 0.003), and age (p-value = 0.012) revealed a significant difference with burnout (BO). Secondary traumatic stress (STS) showed a significant difference with the job location (p-value < 0.001) and nurses' department (p-value = 0.008). Overall, Saudi nurses exhibit high levels of CS and moderate levels of BO and STS.Conclusion: The level of CS was considered good for Saudi nursing professionals; however, the levels of BO and STS require further attention. Enhancing factors related to CS and solving issues related to compassion fatigue (CF) would improve the nursing profession in Saudi Arabia.Keywords: compassion satisfaction, compassion fatigue, burnout, secondary traumatic stress, saudi nurses, Saudi Arabia